NITROGEN FERTILIZER USE IN AGRICULTURE AMONG MARGINAL AND SMALL FARMERS IN INDIA: REVIEW OF IMPORTANT DRIVERSNITROGEN FERTILIZER USE IN AGRICULTURE AMONG MARGINAL AND SMALL FARMERS IN INDIA: REVIEW OF IMPORTANT DRIVERS - Saswat Kumar Pani, Damodar Jena, Rabi Narayan Subudhi, Jyoti Prakash Rath (International Journal of Modern Agriculture, 2021)
Nitrogen, in practice, has been an integral input component in our food production system. The application of synthetic nitrogen in agriculture, which was essential with high yield varieties, has been moving parallel since green revolution. Amendment and regulation of agriculture related acts, polices and extended subsidies have significant link with the different size of farmers to use nitrogen fertilizer. However, sarcastically the intensity of using nitrogen fertilizer in agriculture found to be higher among marginal and small farmers. Moreover, the economic and the environmental cost of production have been increasingly higher than return from agriculture. The economic and environmental implication of increasing nitrogen use lead to issues of declining nitrogen use efficiency, low fertility, economic loss, and decline in soil and water quality. The use of nitrogen fertilizer in agriculture is being driven by various factors related to economic, social, geographical, demographic, institutional, ecological, political and commercial dimensions. However, this paper classifies the nitrogen use drivers, from the existing literature, into price and non-price dimensions. The paper has attempted to answer the following research question through reviewing the related literature and secondary data: what factors drive the marginal and small farmers to use nitrogen fertilizer?